Nível de stress do enfermeiro hospitalar frente a suas competências - Sarturi, Fernanda (2009)
This study aimed to verify the level of stress of hospital nurses, to characterize the population, identify the stressing activities, associate the stressing activities to the level of stress and analyze the correlation between the areas of stress in institutions, compare the level of stress with the socio-demographic variables. This is a field research, exploratory and descriptive with quantitative approach carried out with 214 nurses from two hospitals (A and B) in Santa Maria / RS. For data collection it was used a tool adapted from Bianchi (1990,1999) and Anabuki (2001) - The Daily Stressors Of Hospital Nurses consisting of 55 activities (Likert scale) and 12 socio-demographic questions. The data were stored in a spreadsheet in Excel (version XP) and statistically analyzed using SAS and SPSS softwares. It was performed the standardization of the stress scores, attested the instrument's internal consistency by the Cronbach's alpha coefficient, applied the chi-square test and Kruskal-Wallis, using a significance level of 5% and held the correlation of Spearman. It was found that the Cronbach alpha coefficient is above 0,70; in the institution A the population is female, average age of 42,29 years, working in the institution an average of 13,35 years, and post graduate an average of 82,27%; In institution B the population is female, average age of 33,87 years, working in the institution an average of 6,34 years and post-graduate an average of 73,97%, the variable post-graduate meant a significant difference in the level of stress of the nurses of institution A, the highest score of stress was identified for the activities of the area - working conditions for the performance of activities of nurses, the level of stress is down to 45,39% for the nurses of the institution A and 49,32% for the nurses of the institution B and the competence and skill for general administration and management is associated with all levels of stress. From the results it appears that the hypotheses of this study were confirmed.